Adverse outcomes of cannabis use in Canada, before and after legalisation of non-medical cannabis: cross-sectional analysis of the International Cannabis Policy Study - David Hammond; Anastasia Marquette; Maryam Iraniparast (BMJ Open, 2024)
Objectives To date, there is little evidence on the extent to which cannabis legalisation affects the prevalence of adverse events from cannabis at the population level. The current study examined trends in the prevalence of adverse events among people who consumed cannabis before and after Canada’s legalisation of recreational cannabis.Design Data come from the first four survey waves of the International Cannabis Policy Study, which were conducted online annually immediately prior to non-medical cannabis legalisation in Canada in October 2018, and in the three following years (2019–2021).Participants The current analysis included 18 285 Canadian respondents aged 16–65 who reported cannabis use in the past 12 months.Outcome measures Primary outcomes included types of adverse events experienced from cannabis use, medical help-seeking and the types of products used. Weighted logistic regression models examined differences in help-seeking, emergency room usage and the experience of cannabinoid hyperemesis syndrome across survey years.Results Approximately one-third of people who consume cannabis reported experiencing at least one adverse event within the past 12 months, including 5% of consumers who sought medical help for an adverse event, most commonly for panic attacks, feeling faint/dizzy/passing out, heart/blood pressure problems and nausea/vomiting. The prevalence of seeking help and the types of adverse events were similar before (2018) and after legalisation (2019–2021); however, the proportion of consumers seeking help from emergency rooms increased postlegalisation (F=2.77, p=0.041). Adverse events were associated with various product types, with dried flower and oral oils accounting for the largest proportion of events. Help-seeking associated with cannabis edibles significantly decreased after legalisation (p=0.001).Conclusions Substantial proportions of people who consume cannabis report adverse events, suggesting widespread difficulty in ‘dosing’. Few changes were observed in the prevalence of adverse events reported by consumers since legalisation; however, the location of medical help-seeking and associated products used have changed postlegalisation.